2020
DOI: 10.1002/jcp.29685
|View full text |Cite
|
Sign up to set email alerts
|

PLS3 predicts poor prognosis in pancreatic cancer and promotes cancer cell proliferation via PI3K/AKT signaling

Abstract: Plastin‐3 plays a key role in cancer cell proliferation and invasion, but its prognostic value in pancreatic cancer (PACA) remains poorly defined. In this study, we show that PLS3 messenger RNA is overexpressed in PACA tissue compared with normal tissue. We accumulated 207 cases of PACA specimens to perform immunohistochemical analysis and demonstrated that PLS3 levels correlate with T‐classification (p < .001) and pathology (p < .001). Furthermore, overall survival rates (p < .001) in tumors with high PLS3 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…PLS3 interacts with NFκB repressing factor (NKRF) facilitating its translocation into the nucleus, and thus the transcription of nuclear factor-activated T cells c1 (NFATC1) and an important factor in osteoclastogenesis [16]. Through the PI3K/AKT signaling pathway, PLS3 regulates tumor progression by promoting the proliferation and migration of cancer cells [75].…”
Section: Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…PLS3 interacts with NFκB repressing factor (NKRF) facilitating its translocation into the nucleus, and thus the transcription of nuclear factor-activated T cells c1 (NFATC1) and an important factor in osteoclastogenesis [16]. Through the PI3K/AKT signaling pathway, PLS3 regulates tumor progression by promoting the proliferation and migration of cancer cells [75].…”
Section: Signalingmentioning
confidence: 99%
“…High PLS3 expression is also a feature of pancreatic cancer cells. Here, PLS3 acts as an oncogene and its overexpression triggers the activation of the PI3K/ AKT signaling pathway leading to cancer progression [75]. In non-small-cell lung cancer (NSCLC), increased PLS3 plasma levels are a predictor of poor survival.…”
Section: Malignancies In Solid Tissuesmentioning
confidence: 99%
“…Regarding PLS3, one recent study that included 207 PDA tissue specimens showed that the overexpression of PLS3 was associated with tumor stage and pathology as well as poor OS in PDA patients. PLS3 was an independent prognostic factor in PDA patients [ 14 ]. The authors’ in vitro data demonstrated that PLS3 expression induced PDA cell proliferation and invasion, which were associated with increased PI3K/AKT activity in PDA cells [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…PLS3, also known as T-plastin, is an actin binding protein and not a classical organic anion transporter [ 32 ]. High PLS3 expression has been shown to have poor prognosis in pancreatic cancer, acute myeloid leukemia, gastric cancer, and colorectal cancer [ 33 , 34 , 35 , 36 ]. A direct function of PLS3 as transport protein is not known in the analyzed cancer entities.…”
Section: Discussionmentioning
confidence: 99%